Optical Properties of Natural Armenian and Syrian Zeolites - Harutyunyan, V. V.; Grigoryan, N. E.; Badalyan, A. O.; Arestakyan, A. G.; Soulayman, S. Sh.; Soulayman, G.
he UV-visible (390 – 450 nm) and red-near infrared IR (620 – 800 nm) regions of the spectrum. The excitation is performed using a light of 370 nm of wavelength at temperature equal to 290 K. We conclude from the measurement of optical characteristics that the studied zeolitic samples are of a complex structure and present a complex intergrowth. We also observe the twin cross-form structure of the chabazite crystals.
Keywords: Physics; Cross-Disciplinary